FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN KELENGKAPAN LAPORAN KEUANGAN PADA SEKTOR INDUSTRI MAKANAN DAN MINUMAN (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2013)
The purpose of this study was to examine empirically the factors that affect the completeness of the disclosure of financial statements in the food and beverage industry. Factor in question is DER, CR, ROA, public shares and age of the company. This variable is used to test that the disclosure index company financial statements submitted to the public is a reflection of the state of the companies based on the analysis of financial or quantitative side DER, CR, ROA, public shares and the age of the company without the influence of such qualitative general conditions of the economy , the political situation, the security situation, the market tastes.Samples used in this research is a company engaged in the food and beverage industry. This selection is based on that company in this sector to produce goods that are needed by consumers so that there should be controls that published reports accountable and trustworthy. The sampling method is purposive sample, and after going through the stages penyeleksiaan samples obtained are as many as 11 companies.The empirical results show that not all the variables significantly affect the completeness of disclosure index reports. These results indicate that most companies are not much concerned about the completeness of the disclosure statements given still assume that the goods produced is a necessity for consumers so that it does not require information that is as complete as possible.The purpose of this study was to examine empirically the factors that affect the completeness of the disclosure of financial statements in the food and beverage industry. Factor in question is DER, CR, ROA, public shares and age of the company. This variable is used to test that the disclosure index company financial statements submitted to the public is a reflection of the state of the companies based on the analysis of financial or quantitative side DER, CR, ROA, public shares and the age of the company without the influence of such qualitative general conditions of the economy , the political situation, the security situation, the market tastes.Samples used in this research is a company engaged in the food and beverage industry. This selection is based on that company in this sector to produce goods that are needed by consumers so that there should be controls that published reports accountable and trustworthy. The sampling method is purposive sample, and after going through the stages penyeleksiaan samples obtained are as many as 11 companies.The empirical results show that not all the variables significantly affect the completeness of disclosure index reports. These results indicate that most companies are not much concerned about the completeness of the disclosure statements given still assume that the goods produced is a necessity for consumers so that it does not require information that is as complete as possible.